1991
DOI: 10.1007/bf01871360
|View full text |Cite
|
Sign up to set email alerts
|

Cl/HCO3 exchange in the basolateral membrane domain of rat jejunal enterocyte

Abstract: Basolateral membrane vesicles isolated from rat jejunal enterocyte and well purified from brush border contamination were tested to examine Cl and HCO3 movements. Uptake experiments provided no evidence for a coupling between Na and HCO3 fluxes; K-HCO3 and K-Cl cotransports also could be excluded. Transport studies revealed the presence of a Cl/HCO3 exchanger accepting other anions and inhibitable by the disulfonic stilbenes SITS and DIDS. We can exclude that the evidenced HCO3-dependent Cl uptake is due to br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Previously we demonstrated that (1) in rat jejunum anion exchange is restricted to the basolateral membrane and does not accept ¬_lactate (Orsenigo et al 1991), and (2) rat jejunal basolateral membranes contain a proton-lactate symporter (Orsenigo et al 1997). This evidence, together with the present results, supports the hypothesis that MCT1 is a major route for lactic acid efflux across the basolateral membrane of rat jejunum.…”
Section: Rt-pcr Experimentsmentioning
confidence: 99%
“…Previously we demonstrated that (1) in rat jejunum anion exchange is restricted to the basolateral membrane and does not accept ¬_lactate (Orsenigo et al 1991), and (2) rat jejunal basolateral membranes contain a proton-lactate symporter (Orsenigo et al 1997). This evidence, together with the present results, supports the hypothesis that MCT1 is a major route for lactic acid efflux across the basolateral membrane of rat jejunum.…”
Section: Rt-pcr Experimentsmentioning
confidence: 99%
“…Chlorine uptake (n) at dpi: % Activation 0 3 (12,24,31,40,42). Accordingly, we investigated the effects on 36 Cl Ϫ uptake of imposing gradients of either chloride, pH, or both together in the presence of short-circuiting conditions to assess an electroneutral mechanism.…”
Section: CLmentioning
confidence: 99%
“…We found a Cl/ HCO 3 exchanger (which does not accept lactate) and conductive pathways for both Cl and HCO 3 , but we had no evidence for Na-(HCO 3 ) n cotransport [5][6][7]. The Cl/HCO 3 exchanger probably moves HCO 3 into the serosal fluid, therefore extruding a base into the serosal subepithelial spaces.…”
Section: Discussionmentioning
confidence: 87%
“…Since in the jejunal tract of the intestine HCO 3 absorption occurs (at least in rat, dog, and man) [2][3][4], Cl/HCO 3 exchange should mediate HCO 3 efflux into the serosal compartment. Up to now jejunal basolateral Cl/HCO 3 antiport has been characterized using isolated membrane vesicles [1,[5][6][7][8], demonstrated in isolated enterocytes from the same intestinal tract [9] and not found in the subsequent intestinal tract [10]. Since the maximal activation of Cl/HCO 3 antiport is at about pH 7.2 (preliminary results from our laboratory), under normal conditions the anion exchanger should be involved in bicarbonate transport towards the blood stream.…”
Section: Introductionmentioning
confidence: 99%